Analisis Derajat Deasetilasi Kitosan dari Limbah Cangkang Rajungan dengan Penambahan Variasi NaBH4 dan Suhu - Fatin, Ainiyyah; Salsabilla, Aina; Winarto, Adi Putra; Hakim, Muhammad Fahmi (Peneliti.net, 2024)
Indonesia has a large potential for marine products, namely blue swimming crab. In general, only the part of the crab is processed into food, so crabs have the potential to produce shell waste. So that the use of crab shell waste can be made into chitosan which is done using two approaches, namely providing quality standard values and high selling prices. In the manufacture of chitosan consists of 3 stages, namely (1) Deproteination stage using 3.5% NaOH at 80℃; (2) Demineralization step using 1 N HCl at 30℃; (3) Deacetylation step using 60% KOH solution with the addition of NaBH4 (0.50; 0.75; 1 gram) and temperature (100℃, 110℃, 120℃) with a stirring time of 2.5 hours. From the results of the research that has been done, the best degree of deacetylation was obtained when the addition of 0.75 gram NaBH4 was 73.65% at 120℃. The characteristics of chitosan in the yield with the best 4.25% at 100℃ with the addition of 1 gram of NaBH4. The water content with the best is 5.15% at 110℃ with the addition of 0.75 gram NaBH4. And the ash content with the best is 1.747% at 120℃ with the addition of 0.75 gram NaBH4